Directional Airflow and Ventilation in Hospitals: A Case Study of Secondary Airborne Infection() - Mousavi, Ehsan S. (Energy Procedia, 2015)
Since the 1990s, improvements in ventilation techniques and isolation procedures have been widely credited with the decline in nosocomial transmission of tuberculosis and other airborne diseases. Little effort, however, has been made to study the risk of isolation patients acquiring secondary infections from contaminated air migrating into negatively pressurized isolation rooms from adjacent spaces. As a result, an actual hospital was used to observe the transport of aerosol from a nursing station and general patient room to a nearby airborne infectious isolation room (AIIR). Aerosols ≤3.0 μm (viruses and most airborne bacteria) were found to be capable of migrating 14.5m from a general patient room to an AIIR anteroom entrance in <14 minutes at concentrations 2-5 times greater than ambient (e.g. background). Concentrations of aerosols within the anteroom and isolation room, however, remained virtually unchanged from ambient levels, indicating the effectiveness of door position and (or) ventilation. In contrast, gravitational settling and surface deposition appeared to limit the migration of aerosols >3.0 μm to the entrance of the general patient room (4.5m).